Rapid, energy-efficient and pseudomorphic microwave-induced-metal-plasma (MIMP) synthesis of Mg2Si and Mg2Ge - Fan, Zhen; Ho, Hsi-Nien; Szczęsny, Robert; Wei-Ren, Liu; Gregory, Duncan H (CrystEngComm, 2022)
Polycrystalline magnesium silicide, Mg2Si and magnesium germanide, Mg2Ge were synthesised from the elemental powders via the microwave-induced-metal-plasma (MIMP) approach at 200 W within 1 min in vacuo for the first time. The formation of reactive Mg plasma facilitated by the high-frequency electromagnetic field (2.45 GHz) is at the origin of the ultrafast reaction kinetics in these preparations. Powder X-ray diffraction (PXRD), Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-ray Spectroscopy (EDX) and X-ray Photoelectron Spectroscopy (XPS) attest to the high purity of the products. Both SEM and Transmission Electron Microscopy (with Selected Area Electron Diffraction) (TEM/SAED) demonstrate the pseudomophic nature of the metal plasma reactions such that use of nanoporous Ge starting material leads to the production of nanoporous germanide, Mg2Ge. Covalent Mg–Si and Mg–Ge bonds with partial ionic character are suggested by XPS, while the refined crystal structures are consistent with Mg–Mg interactions within the cubane-like clusters in Mg2X antifluorite unit cells. The MIMP method unlocks not only the sustainable synthesis of Mg2X materials but also the wider production of intermetallics and Zintl phases of prescribed morphology.